Cili Sedap Enterprise / Saperuddin Mohd Noor... [et al.] - Mohd Noor, Saperuddin; Asidin, Arnin; Norman, Mohd Fairul Rezza; Mohd Najib, Mohd Said (Faculty of Business Management, 2010)
Chilly is one of the additional foods and a good prospect as a source of income. It is also a product with a high demand either as flavor production or any product such as samba! and other confectionery products. So, we choose to produce chilly as our main production. Chilly is one of the oldest fruits in the world. It is already being cultivated by Ecuador people 6000 years ago. It available almost throughout the year, the chilly is a nutritious, palatable, fiery hot flavor, which is rich in vitamin C, carotene ( pronvitamin A), and minerals. Not only that, it is one of the additional foods and a good prospect as a source of income. Chilly has been successfully introduced throughout Asia and Pacific and is now an important crop. It grows easily in almost any soil, and event extremely dry condition. Often regarded as a subsistence crop, Chilly is not always available in big city market. According to press trusts of India (2009), Malaysia becomes are second largest their importer in the industry of Indian spices, after united kingdom, with it's imports worth $79 millions in 2009. In this statement, Malaysia will become a second largest exporter chilies industry in the world. Kementerian pertanian dan industry asas tani Malaysia reported that more farmer now switch into chili industry. In their official website tells.a farmer turned to the chili industry and described get a healthy profit earned from the first crop. Besides that's, chili industry has high potential industry to develop in Malaysia because the khatulistiwa climate very suitable for chili. Farming nowadays is seen as an alternative source of income rather than working in offices as young executives. Modern farming and 'cili fertigatisi' or chilli fertigation has become an attraction to fresh graduates to get involved in this lucrative business. In Malaysia nowadays, modem farming is now considered as a 'business' instead of just a traditional village work. It is a popular trade as the market price for fertigated chilli has risen from RM1 per kilogram into RM20-25 per kilogram in big cities such as Kuala Lumpur. Financial institution is also currently making agro-based loans available to help these young entrepreneurs finance their projects. Cili Fertigasi in Malaysia is growing in the rural area of the country and you can take part in this process too. CILI SEDAP ENTERPRISE more focuses to plant red-green chilly in the family solanaceae also known as capsicum annum-red chili. According the analysis that we made from articles, this species more valuable and have highest demand in the market.